The Price of Everything : A Parable of Possibility and Prosperity - Roberts, Russell D. (Book collections on Project MUSE., 2008)
Stanford University student and Cuban American tennis prodigy Ramon Fernandez is outraged when a nearby mega-store hikes its prices the night of an earthquake. He crosses paths with provost and economics professor Ruth Lieber when he plans a campus protest against the price-gouging retailer--which is also a major donor to the university. Ruth begins a dialogue with Ramon about prices, prosperity, and innovation and their role in our daily lives. Is Ruth trying to limit the damage from Ramon's protest? Or does she have something altogether different in mind? As Ramon is thrust into the national.